2022
DOI: 10.3758/s13415-022-01017-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal maturation of resting state networks: Relevance to sustained attention and attention deficit/hyperactivity disorder

Abstract: The transition from childhood to adolescence involves important neural function, cognition, and behavior changes. However, the links between maturing brain function and sustained attention over this period could be better understood. This study examined typical changes in network functional connectivity over childhood to adolescence, developmental differences in attention deficit/hyperactivity disorder (ADHD), and how functional connectivity might underpin variability in sustained attention development in a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…This observation from our data is consistent with evidence that longer intervals between these two points in the order of years can reveal significant changes in the RT. Recently, Thomson et al (2022), examined the longitudinal maturation of resting state networks in Individuals with ADHD compared to controls at three time points across ages 9 to 14 years. They found that the ADHD group displayed more significant decreases in functional connectivity between salience and visual networks compared with controls and a reduction in RT at 13.2 years compared with the age of 10.4 years in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation from our data is consistent with evidence that longer intervals between these two points in the order of years can reveal significant changes in the RT. Recently, Thomson et al (2022), examined the longitudinal maturation of resting state networks in Individuals with ADHD compared to controls at three time points across ages 9 to 14 years. They found that the ADHD group displayed more significant decreases in functional connectivity between salience and visual networks compared with controls and a reduction in RT at 13.2 years compared with the age of 10.4 years in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also suggested that the significant interindividual variability in ADHD could be related to different alterations in brain structure and function (Chiang et al, 2022; Kölle et al, 2022; Lin et al, 2014; Thomson et al, 2022; Tremblay et al, 2020). These studies show how interindividual similarity inferred by interindividual variability can be investigated in individuals with ADHD using neuroimaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study by DeSerisy et al (2021) found connectivity between DMN and FPN brain regions were increasingly anticorrelated in older participants (age range: 7–25 years), suggesting between-network segregation in these networks. Additionally, Thomson et al (2022) found decreased SN-FPN and SN-DMN network connectivity in children. As such, a tenet in the existing literature is that by adulthood brain regions within-network show stronger correlations with each other, whereas brain regions that are from different networks show weaker correlations, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…Results from a more recent cross-sectional study by Sanders et al (2023) further supports the tenet that age-related increases in within-network connectivity occur in DMN and FPN but decreases occur in within-network connectivity in the SN during childhood and into early adolescence. As for between-network connectivity, current evidence points to segregation for all canonical networks, namely those within the triple network model (FPN, SN, DMN) ( DeSerisy et al 2021 ; Thomson et al 2022 ). For example, a recent study by DeSerisy et al (2021) found connectivity between DMN and FPN brain regions were increasingly anticorrelated in older participants (age range: 7–25 years), suggesting between-network segregation in these networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation